PENGARUH LAYANAN BIMBINGAN KELOMPOK TERHADAP PENINGKATAN BERPIKIR POSITIF SISWA KELAS X MIA 7 MAN 2 MODEL PEKANBARU TAHUN AJARAN 2015/2016 - Payeni '; Elni Yakub; Zulfan Saam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract:Cognitive development indicates the development of students’ way of thinking. Students’ability in coordinating the ways of thinking in order to solve various problemscanbeappliedas The Score Range of growing intelligence. The low of students’ positive thinking indicates students’ behavior that far from the concept of positive thinking as they have not hadpositive self-concept yet. The objective of this research is to find out the impacts ofgroup guidance and counseling services to students’ positive thinking of the experimental group. Themethod of this researchis real-experimental method with the pattern of pretest-posttest control group design. The subject of this research is 20 students of grade X MIA 7 MAN 2 ModelPekanbaru which have low positive thinking. The technique of data analyzing in this research use three formulas, namely the formula of Wilcoxon Experiment, Spearman Rank Experimentand Man Whitney Experiment. Based on the hypothesis experiment by applying SPSS 16.0, it is obtained that the value of sig. (2-tailed) is 0.023. Due to the fact that the value of sig. (2-tailed) fewer than the α value (0.023< 0.05),thus it can be concluded that “There is positive impact that significant in giving group counseling services to the improvement of students’ positive thinking”. The impact of group counseling services in improving students’ positive thinking give medium contribution, that is 49,6%.Keywords: group guidance services, positive thinking